(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2018)
To construct the binding isotherms of nucleic acid–ligand it is necessary to determine physical characteristics of completely bound state of ligand (Ab) experimentally. It is often impossible to determine Ab experimentally, due to which as Ab the value of the parameter is accepted, which almost does not change in the experiment error framework. Calculations show that in this case the binding constant determination error does not exceed 10%.